Representasi Penyatuan Kelurga Pada Tradisi Perkawinan Ngulihi Tudung Suku Karo Kajian: Semiotika Roland Barthes - Arini Karo-Karo; Abdurahmahman Adisaputra (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to describe the meaning of denotation, meaning of connotation, and myth in the traditions of Ngulihi Tudung in the Karo tribe. This study is a qualitative descriptive study by applying a semiotic approach developed by Roland Barthes to uncover aspects of sign communication in the marriage tradition of Karo Ngulih Tudung which later differed from the public view of marriage traditions that began to be distorted. The data obtained in this study is a sentence, dialogue or sign that can communicate the message to be delivered to the marriage tradition of Ngulihi Tudung tribe Karo. The data analysis technique is to carefully identify signs and symbols in the Tudung Tradition, divide them into markers and markers, analyze the relationship of signs to form more complex meanings, analyse the meaning of denotations, analyse meaning of connotations based on cultural historical context to mythology as ideology based on the study of Roland Barthes' Semiotics, and write the conclusions of the research. The results of the study show that the meaning of the denotation in the marriage tradition of Ngulihi Tudung seeks to show the most tangible meaning in the sign. In other words, the Denotation of Roland Barthers in the sentence found in the Marriage tradition is what is described by the sign against an object. Connotation is expressive, involving more subjective and objective experience. In the marriage tradition Ngulihi Tudung invites the public to criticize as sharply as myths can see certain values or norms that work in society.